2019
DOI: 10.3390/pharmaceutics11100495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Traditional and Ultrasound-Enhanced Electrospinning in Fabricating Nanofibrous Drug Delivery Systems

Abstract: We investigated nozzleless ultrasound-enhanced electrospinning (USES) as means to generate nanofibrous drug delivery systems (DDSs) for pharmaceutical and biomedical applications. Traditional electrospinning (TES) equipped with a conventional spinneret was used as a reference method. High-molecular polyethylene oxide (PEO) and chitosan were used as carrier polymers and theophylline anhydrate as a water-soluble model drug. The nanofibers were electrospun with the diluted mixture (7:3) of aqueous acetic acid (90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…formation of ultrasound fountain relative to applied electric field, generation of capillary waves by ultrasound, cavitation, acoustic streaming, and thermal effects [43]. Similarly, Hakkarainen et al [44] have investigated fabrication of nanofibers using USES and compared with the one synthesized using the traditional electrospinning method for drug delivery applications. The nanofiber generated using USES had higher fiber diameter of 402 ± 127 nm over 77 ± 21 nm fiber synthesized using traditional method.…”
Section: Ultrasound-enhanced Electrospinning (Uses)mentioning
confidence: 99%
“…formation of ultrasound fountain relative to applied electric field, generation of capillary waves by ultrasound, cavitation, acoustic streaming, and thermal effects [43]. Similarly, Hakkarainen et al [44] have investigated fabrication of nanofibers using USES and compared with the one synthesized using the traditional electrospinning method for drug delivery applications. The nanofiber generated using USES had higher fiber diameter of 402 ± 127 nm over 77 ± 21 nm fiber synthesized using traditional method.…”
Section: Ultrasound-enhanced Electrospinning (Uses)mentioning
confidence: 99%
“…A comparative study of traditional electrospinning (TES) with ultrasound enhanced electrospinning (USES) has been conducted for the formulation of a nanofiber drug delivery system using polyethylene oxide (PEO) and chitosan as carrier polymers and theophylline anhydrate as a water-soluble model drug. The results showed that NFs produced by USES were amorphous compared to those produced by TES [ 92 ]. A very promising novel application of the free-surface method has been manipulated by combining the alternating current electrospinning (ACES)—instead of using direct current—with centrifugal force, and a higher throughput has been obtained [ 93 ].…”
Section: Up-scaling Of Nanofiber Productionmentioning
confidence: 99%
“…Now we predict the acoustic streaming inside the polymer solution. Different ultrasound driving parameters affect the produced fibers' diameter in USES [5] and as such, we expect that acoustic streaming could be one of the phenomena related to this.…”
Section: Introductionmentioning
confidence: 97%